Recent Trends in Algebraic Development Techniques 19th International Workshop, WADT 2008, Pisa, Italy, June 13-16, 2008, Revised Selected Papers - Corradini, Andrea; Montanari, Ugo (Theoretical Computer Science and General Issues, 2009)
This book constitutes the thoroughly refereed post-conference proceedings of the 19th International Workshop on Recent Trends in Algebraic Development Techniques, WADT 2008, held in Pisa, Italy, on June 13-16, 2008. The 18 revised full papers presented together with 3 invited talks were carefully reviewed and selected from 33 presentations at the workshop. The papers focus on the algebraic approaches to the specification and development of systems, and address topics such as formal methods for system development, specification languages and methods, systems and techniques for reasoning about specifications, specification development systems, methods and techniques for concurrent, distributed and mobile systems, and algebraic and co-algebraic foundations.